Interacción comunicativa y cultura organizacional (2004)
This article is an approach to the concepts of Culture and organizational culture from different theoretical perspectives. Furthermore, it aims at establishing a relationship between the notions on communicative interaction and organizational culture, expounding two possible hermeneutic models in order to approach such an issue.